Annotations to handball in the historical context of sport in Spain (1900-1939) - Xavier Torrebadella-Flix (Federación Extremeña de Balonmano; University of Extremadura, 2013)
To address the origins of handball in Spain, studying new historical documentary sources allows us to state the question and describe or reinterpret events so far known. The handball was introduced through the Explorers from Spain, Central School of Gymnastics and mainly by women's sports at the University of Madrid during the Second Republic. The news presented here helps build the history of handball in the social situation of sport in Spain from 1900 to 1939.